Institutional framework for promoting and supporting small, micro and medium enterprise in South Africa: supply perspective - Sishuba, Ludumo Christian (Graduate School of Business (GSB), 2021)
All around the world, many studies demonstrate the importance of Small, Micro and Medium Enterprises (SMMEs) in lifting-up the economy and creating employment. Many governments around the world have created institutions with the aim to enhance SMME survival and growth. This in turn contributes to social and political stability in a country. Despite the importance of SMMEs to the economy and employment creation, in South Africa studies (Hallberg, 2000; World Bank, 2000; World Bank, 2007; SBP, 2014; GEM, 2015, & Edinburg Group, 2015) show that government policy hinders the development and growth of SMMEs. One of the most cited government policies that hinder SMME development and growth is the institutional framework. Institutions are viewed as the platform that could be used to apply formal and/or informal “rules of the game” in society. These institutions play a critical role for the individuals and organisations (our emphasis) to manage unforeseen events, outcomes and high transaction costs. In order for the institutional platforms to remain relevant, it is critical that they are developed to meet the needs of entrepreneurs and SMMEs, since in actual fact they are the ones, which need the institutional platforms for growth. The National Planning Commission through the National Development Plan (NDP, 2013) stresses the need for South Africa to create a conducive business environment. This means eliminating policy and regulatory constraints in order to accelerate development and growth of SMMEs. It is also stated that the institutional matrix plays a crucial role to ensuring that organisations remain viable, profitable and survive growth phases. To experience successful change process, organisations need to appreciate the constraints that hinder development. Hence it is important to ensure that governments create business environment that respond to the needs of the SMMEs. The aim of the study was to examine the current South Africa's institutional framework for SMMEs and find out if the designed and implemented programmes appropriately meet the demands of SMMEs in South Africa. The objectives of the study were to review various institutional frameworks for promoting and supporting SMMEs that are promoting and supporting SMMEs around the world and in South Africa; to assess the extent to which SMMEs support institutions were designing and implementing support services and strategies that responded to the short- and long-term needs of SMMEs. The research study found that the key institutional constraints perceived by public sector service providers as inhibiting the development of SMMEs in South Africa are the following: there is low coordination between organizations supporting SMMEs; inadequate management skills, in particular financial management; lack of domestic and global market access; high regulatory burden, to clear the red tape and lack of access to information and technology infrastructure. This research study advances that solid institutions can help to improve and enhance the role of SMMEs in meeting government's developmental objectives. This view was enabled by the research approach to gather primary information from public sector experts supporting SMMEs, but it also affirms that the views narrated would be subjective. The research study argues that South Africa has a relatively developed institutional framework that supports growth and development of SMMEs. However, the plethora of government programmes administered in various levels of government; different departments and agencies coupled with limited resources has caused fragmentation. The findings in this research study show that government agencies including their oversight holding departments have shown substantial overlap indications in terms of their programmes offering. Further, the findings indicate that there is inadequate interaction with the private sector, SMMEs associations, higher education institutions including civil societies in designing programmes, as result the needs of SMMEs are not properly considered. It essential to improve partnerships in programmes that support export promotion, innovation and training and development. The research study further proposes that South Africa, should adopt and adapt the institutional structures applied in Malaysia and the United States of America (USA). Their institutional structures support a high level body that includes both the political representation and private sector, SMMEs associations, higher education institutions including civil society representation in its composition. This way, social partners would be enabled to influence policy and programme development in relation to the SMME industry. The thesis emphasises the important role of a partnerships approach in implementing development programmes. Further, the thesis argues that what is vital is to listen and incorporate the needs of the business owners, and ensure that policies and programmes meet the expectations of the SMMEs.